2018
DOI: 10.1039/c8ra06094k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement in electrical conductivity and Seebeck coefficient of PEDOT:PSS by N2pressure-induced nitric acid treatment

Abstract: As a thermoelectric (TE) material suited to applications for recycling waste-heat into electricity through the Seebeck effect, poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonic acid) (PEDOT:PSS) is of great interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…18 Nonetheless, the degradation and stability of p-type doped organic semiconductors have received limited attention. 19,[23][24][25][26][27] Although p-type organic semiconductors are generally regarded as air-stable, there are a few degradation pathways such as water absorption and diffusion of molecules with small sizes or low boiling point, which leads to the creation of trap states or morphological changes in the microstructure of the OSC. [28][29][30] Formic acid (FA) is a common dopant for PEDOT:PSS, which makes a clear example of such a mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…18 Nonetheless, the degradation and stability of p-type doped organic semiconductors have received limited attention. 19,[23][24][25][26][27] Although p-type organic semiconductors are generally regarded as air-stable, there are a few degradation pathways such as water absorption and diffusion of molecules with small sizes or low boiling point, which leads to the creation of trap states or morphological changes in the microstructure of the OSC. [28][29][30] Formic acid (FA) is a common dopant for PEDOT:PSS, which makes a clear example of such a mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…1, it was found that the PF was increased to 76.0 AE 5.3 mW m À1 K À2 for the N-PEDOT:PSS film, mainly attributable to the remarkably enhanced s value. 46,47 The N-PEDOT:PSS film treated with an ionic liquid [bmim] [OTf] or [bmim][BF 4 ] caused the decline in s value from 3200 AE 89 to 1260 AE 61 and 1188 AE 45 S cm À1 , respectively. The S of the N-PEDOT:PSS film was 16 AE 1.2 mV K À1 , which was faintly smaller than that of the untreated PEDOT:PSS film.…”
Section: Resultsmentioning
confidence: 99%
“…71 The remarkable enhancement in its crystallinity was also supported by the AFM images, being in good agreement with the reported results. 46,47,71,72 By comparison, for the ]-N-PEDOT:PSS films exhibit improved interchain coupling of PEDOT:PSS chains with more densely packed PEDOT and lamella stacking between two types of assemblies, leading to enhanced S of the PEDOT:PSS films through interface scattering. 71,73,74 Interface scattering includes surface scattering and grain boundary scattering.…”
Section: Characterization Of Te Properties Of Pedot:pss Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published by Wiley-VCH GmbH Kim et al [68] PEDOT:PSS BSA DMSO, HZ Phase separation 1996 203 4.6 Wang et al [69] PEDOT:OTf NaOH RedOx, doping/ dedoping 49 2342 570 Yao et al [70] PEDOT:PSS IL Mixture of IL Soret effect 17 520 15 Mazaheripour. [71] PEDOT:PSS N 2 gas 30 1200 94 Zar Myint et al [72] PEDOT:PSS PEIE H 2 SO 4 Doping/ dedoping 24 2800 133 Li et al [73] PEDOT Ni et al [74] P3HT CNT Iodine Redoping 29 1722 148 Tonga et al [75] P3HT Kang et al [76] P3HT Sb 2 Te 3 F4TCNQ 102 1.78 1.6 Jang et al [77] P3HT MoO 3 , PbS quantum dots…”
Section: (22 Of 26)mentioning
confidence: 99%